Did Women and Candidates of Color Lead or Ride the Democratic Wave in 2018?. Issue 3 (July 2020) - Fraga, Bernard L.; Shah, Paru; Juenke, Eric Gonzalez
Abstract : Headlines touted a "wave" of women and minority candidates running in the 2018 elections, leading some to conclude that 2018 was the new "year of the woman" and perhaps "year of the candidate of color" (Lai et al. 2018). In fact, the number of women and candidates of color contesting US House elections was so high in 2018 that for the first time on record, White men were the minority of Democratic House nominees (Schneider 2018). Surveys taken immediately before the 2018 midterm elections indicated that women of color were the "ideal candidates" for Democrats, suggesting a changing voter demand for a more diverse field of candidates (Easley 2018).